Performance Strategy Analysis of Employees at PT. Perkebunan Nusantara III (Persero) Medan - Muhammad Agung Anggoro; Bill Clinton Sinaga; Siti Fadillah Nasution; Rosalin Apriani Br. Sigiro; Janne Nita Ria Br. Purba (Budapest International Research and Critics University, 2022)
Companies generally really need quality human resources to achieve predetermined company goals, in achieving these goals, the company's human resources need to be managed professionally in order to realize a balance between the needs of employees and the demands and capabilities of the company's organization. Thus, this study aims to examine and analyze the effect of work discipline on employee performance, analyze work motivation on employee performance, and analyze the work environment on employees. Sources and data collection techniques used in this study are primary data, namely data obtained or collected directly from data sources through interviews and a list of questions given to respondents. The results showed that work discipline was not significant on employee performance. Motivation has a positive effect on employee performance. The work environment has a positive effect on employee performance.